Rozwiązane

Doprowadź do najprostszej postaci.

a) (√5-2√3 )^2-(√3-√5 )^3+2(1-√15)
b) (1-√3 )^3-(2-√2 )^3-2(1-√2)(1+√2)
c) (2-2√3 )^2-(1-√3 )^3+(1-√3)(1+√3)
d) 2(1-√5 )^3-(1+√3)(√3-1)

Proszę o jak najszybsze rozwiązanie.



Odpowiedź :

a)(√5-2√3 )^2-(√3-√5 )^3+2(1-√15)= (6-2*√5*2√3+(2√3)^2)-3√3-5√5+2-2√15=5-4√15+12-3√3-5√5+2-2√15=19-6√15-3√3-5√5

b)(1-√3 )^3-(2-√2 )^3-2(1-√2)(1+√2)=1-√27-8-√8-2(1-√2)=1-3√3-8-2√2+2√2-2=-9-3√3

c)(2-2√3 )^2-(1-√3 )^3+(1-√3)(1+√3)=(4-8√3+12)-1+√27+1-√3=16-8√3+3√3-1√3=16-6√3

d)2(1-√5 )^3-(1+√3)(√3-1)=2-2√125-√3-1=2-10√5-√3-1=1-10√5-√3